Морфо-анатомічні показники хвої Pinus pallasiana D. Don. у різних лісорослинних умовах протиерозійного насадження - Бессонова, Валентина Петрівна; Bessonova, Valentina; Юсипіва, Тетяна Іванівна; Iusypiva, Tetyana (ALEX MATSYURA PRESS, 2018)
Досліджено морфо-анатомічні показники асиміляційного апарату сосни Палласова (Pinus pallasiana D. Don.) в різних лісорослинних умовах протиерозійного насадження в умовах степового Придніпров’я. Пробні площі відрізнялися лісорослинними умовами, особливо рівнем забезпечення вологою. Виявлено зміни кількісних показників асиміляційного апарату P. pallasiana в сухих лісорослинних умовах. Показано зменшення як морфометричних характеристик (довжина, ширина та товщина хвоїнки), так і анатомічних параметрів (розміри провідних пучків, кількість смоляних ходів, товщина шару складчастої паренхіми). Встановлено адаптивні зміни асиміляційного апарату P. pallasiana до нестачі вологи: утворення більш товстої кутикули, збільшення товщини клітин епідерми та гіподерми, що знижує втрати вологи. The paper studies morpho-anatomical parameters of the needles of Pinus pallasiana D. Don. in different forest growth conditions of the antierosion afforestation in the steppe Prydniprovya. The research objects are 25-27-year-old plants, which grow in cross-sectional rows on the northern slope of wooded ravine Viyskovyi. The test Plots differ in forest growth conditions especially in the extent of water supply.In spite of the relatively high drought tolerance of P. pallasiana, such morphometric indices of needles as length, width and thickness are reduced in dry forest conditions. Quantitative changes in a number of indicators of the structural elements of the anatomical structure of the needles indicate adaptive changes to the lack of moisture. The formation of needles in dry forest conditions causes the formation of a thicker cuticle, an increase in the thickness of the cells of the epidermis and the hypodermis (radially in the transverse section), which reduces the loss of moisture. However, reducing the size of the conducting beams limits both the flow of water into the needle and the outflow of assimilates. In arid growing conditions, the number of resin canals in needles is reduced compared to plants of thalweg, the layer of folded parenchyma, both the adaxial and abaxial parts of the needles, is thinned.
Morpho-anatomical parameters of the needles of Pinus pallasiana D. Don. in the antierosion afforestation
Keywords: протиерозійні насадження; antierosion afforestation; лісорослинні умови; forest growth conditions; Pinus pallasiana; Pinus pallasiana; хвоя; needles; морфометричні і анатомічні показники; morphometric and anatomical parameters